Gross efficiency and the relationship with maximum oxygen uptake in young elite cyclists during the competitive season - Artetxe-Gezuraga, X.; Maldonado-Martin, S.; Freemye, B. G.; Cámara, J. (Journal of Human Kinetics, 2019)
This study assessed gross efficiency (GE) during a single competitive season and determined the relationship between GE and maximum oxygen uptake (VO2max) in young elite cyclists (n = 15, 20.1 ± 1.4 yrs, 177.5 ± 5.7 cm, 68.3 ± 6.2 kg, 45.2 ± 7.5 mm of six skinfolds) during a competitive season. Participants completed at two occasions (T1 = April; T2 = July), a progressive bike protocol (initial intensity = 100 W, 35 W increments every 3 min) until volitional exhaustion to assess VO2max and submaximal variables. A single capillary blood sample was drawn from the left earlobe immediately after completion of each exercise load to determine lactate thresholds. Cyclists` GE was calculated as ([work accomplished/energy expended] x 100). No significant differences were obtained in GE at any workload between T1 and T2 or in the mean GE between T1 (19.3%) and T2 (19.4%) testing (p = 0.93). No significant association was found between mean GE and VO2max at either T1 (r = -0.28, p = 0.30), or T2 (r = -0.27, p = 0.32). GE of young elite cyclists might not vary during the most important phase of the training season and GE was not related to VO2max. A lower accumulated volume and intensity of training of these cyclists may account for their lower GE in comparison to older professional cyclists and might not have been enough to foster higher increases of GE in cyclists with lower VO2max.